Technological Literacy and Its Relationship to Job Performance of primary school principals - Lect. Adnan Ali Hussain (Journal of College of Education, 2025)
The purpose of this research aims to identify the technological literacy and its relationship to job performance of primary school headmasters. The descriptive correlational approach was adopted by the researcher according to technological literacy scale of Tharthar (2018), which consisted of (80) items. Also, the researcher adopted the job performance scale of Montaser (2020), and the scale consisted of (19) items. The research sample consisted of (175) primary school headmasters. The most prominent results of the research were the presence of statistically significant differences, which shows that school headmasters have a high degree of technological literacy that exceeds the average, and they also have a high degree of job performance. The correlation is positive between the research variables, and there are differences in the relationship according to gender in favor of females. The research came out with a number of recommendations and suggestions.